Chemical Characterization of Fruit Wine Made from Oblačinska Sour Cherry - Milica Pantelić; Dragana Dabić; Saša Matijašević; Sonja Davidović; Biljana Dojčinović; Dušanka Milojković-Opsenica; Živoslav Tešić; Maja Natić (The Scientific World Journal)
This paper was aimed at characterizing the wine obtained from Oblačinska, a native sour cherry cultivar. To the best of our knowledge, this is the first paper with the most comprehensive information on chemical characterization of Oblačinska sour cherry wine. The chemical composition was characterized by hyphenated chromatographic methods and traditional analytical techniques. A total of 24 compounds were quantified using the available standards and another 22 phenolic compounds were identified based on the accurate mass spectrographic search. Values of total phenolics content, total anthocyanin content, and radical scavenging activity for cherry wine sample were 1.938 mg gallic acid eqv L−1, 0.113 mg cyanidin-3-glucoside L−1, and 34.56%, respectively. In general, cherry wine polyphenolics in terms of nonanthocyanins and anthocyanins were shown to be distinctive when compared to grape wines. Naringenin and apigenin were characteristic only for cherry wine, and seven anthocyanins were distinctive for cherry wine.